2005
DOI: 10.1007/s00395-005-0547-2
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant N–terminal fragments of chromogranin–A modulate cardiac function of the Langendorff–perfused rat heart

Abstract: In this study we tested the hypothesis that vasostatins could act as myocardial modulators in the mammalian heart. Using the Langendorff-perfused rat heart, the cardiac effects of the two recombinant human CGA N-terminal fragments STA-CGA1-78 and STA-CGA1-115, containing the vasostatin-1 (CGA 1-76) and vasostatin-2 (CGA 1-113) sequences, respectively, were evaluated at concentrations of 11 / 165 nM. Cardiac performance was evaluated by analyzing left ventricular pressure (LVP) and the rate pressure product (RP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
82
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(94 citation statements)
references
References 31 publications
11
82
1
Order By: Relevance
“…Therefore, it has been suggested that VSs, in addition to their vasoinhibitory properties, are cardioregulatory mediators; i.e., they are able to exert an antiadrenergic action that could protect the heart against intense excitatory stimulations, such as those elicited by the stress response (9,11,19,26).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, it has been suggested that VSs, in addition to their vasoinhibitory properties, are cardioregulatory mediators; i.e., they are able to exert an antiadrenergic action that could protect the heart against intense excitatory stimulations, such as those elicited by the stress response (9,11,19,26).…”
Section: Discussionmentioning
confidence: 99%
“…All drug-containing solutions were prepared fresh before the experiments. We used recombinant human VS-1 [STA-CgA-(1-78)] containing the VS-1 peptide (1-76) previously described (9). The rat CgA sequence is identical in that region to the human sequence.…”
Section: Animalsmentioning
confidence: 99%
See 2 more Smart Citations
“…The major VSinduced actions consist of both negative inotropism (eel, frog, rat) and lusitropism (rat) and of the relevant counteraction of the bARs-mediated positive inotropism, typically induced by ISO (eel, frog, rat), achieved through a functional non-competitive type of antagonism (Fig. 5) Imbrogno et al, 2004;Cerra et al, 2006;Pieroni et al, 2007). As detailed in the rat heart, these effects are independent of f H and coronary performance and are comparable to those documented in the trabeculate and luminally supplied eel and frog hearts.…”
Section: Qkkhsgfedelsevlenqssqaelkeaveepsskdvmekrmentioning
confidence: 99%